Manifestations, Causes, and Governance of Data Monopoly in Chinese Internet Platforms - Xinyue Huang (Law and Economy, 2023)
Data has become a critical factor of production in China’s digital economy development. Internet platforms, in their pursuit of market dominance, engage in data monopolies that impede the healthy growth of the market economy. Data monopolies on internet platforms manifest in various forms, posing threats to other market entities and consumers’ rights. The formation of platform data monopolies can be attributed to the nature of data itself, as well as deficiencies in government and legal regulations. Although laws such as the Anti-Monopoly Law and the Price Law provide certain regulations and government oversight, the current provisions are disconnected from practical implementation, resulting in limited effectiveness in governing platform data monopolies. To eliminate adverse factors that hinder fair market competition and protect consumers’ legitimate rights, this paper argues for governance principles based on marketization and the rule of law. It suggests establishing clear governance rules for platform obligations and adopting a governance approach that combines corporate self-governance, government regulation, and social supervision.